ASSISTANCE IN MAPPING THE FUNCTION OF THE AREA AND LAND CAPABILITY OF GANGGA DISTRICT - Widayanti, Baiq Harly; Susanti, Febrita; Ridha, Rasyid; Yunianti, Sri Rahmi (JCES (Journal of Character Education Society), 2022)
Abstrak: Kecamatan Gangga yang berbatasan dengan perkotaan Tanjung memiliki permasalahan dalam alih fungsi lahan menjadi kawasan permukiman. Tujuan pengabdian ini untuk mendampingi pihak kecamatan Gangga sehingga memiliki peta fungsi kawasan dan peta kemampuan lahan sebagai arahan untuk pemilihan lokasi bermukim yang aman. Metode yang digunakan dengan memanfaatkan peta dasar yaitu:  jenis tanah, curah hujan, morfologi, erosi, kebencanaan dan kestabilan lereng. Keakuratan data yang diolah diverifikasi dengan survey primer dan berdasarkan informasi dari masyarakat setempat. Peta tersebut dioverlay sehingga menghasilkan peta fungsi kawasan dengan pembagian kawasan budidaya seluas 112,23 (55,21%) dan fungsi lindung 91,06 (44,79%). Peta fungsi kawasan dan kemampuan lahan dijadikan acuan oleh pemerintah Kecamatan Gangga dalam memberikan ijin pengembangan kawasan permukiman. Pengembangan kawasan permukiman dapat dilakukan pada kawasan budidaya. Hasil pengabdian ini kemudian disosialisasikan kepada masyarakat agar mereka paham terkait dengan arahan pengembangan kawasan permukiman yang telah ditetapkan.Abstract:  Gangga district bordering the Tanjung city, has problems in converting land functions into residential areas. The purpose of the activity is to accompany the Gangga district so that it has a map of the function of the area and a map of land capabilities as rules for safe settlement locations. The method uses the base map, namely: marbles, soil type, rainfall, morphology, erosion, disaster and slope stability. The method uses the base map, namely: soil type, rainfall, morphology, erosion, disaster and slope stability. The accuracy of the processed data is verified by primary surveys and based on information from the local community. The base map was covered, resulting in a cultivated area of 112.23 (55.21%) and a protected area of 91.06 (44.79%). The map of the function of the area and the ability of the land is used as a rule by the Gangga District government in issuing permits for the development of residential areas. The development of residential areas can be carried out in cultivated areas. The results of the activities are socialized to the community so that they understand related to the rules for the development of predetermined residential areas.